'Black Bone' magnetic resonance imaging as a novel technique to aid the pre-operative planning of posterior tympanotomy for cochlear implantation. (2nd January 2021) - Connor, S. E. J.; Borri, M.; Pai, I.; Barnsley, H.
Abstract : Purpose: 'Black Bone' magnetic resonance imaging (BB MRI) is a novel sequence developed as an alternative to computed tomography (CT) for osseous imaging. We explored its potential utilisation in the pre-operative surgical planning of posterior tympanotomy for cochlear implantation through depiction of the mastoid facial nerve (mFN) canal and the posterior canaliculus of the chorda tympani (ChT), thus defining the facial recess. Methods: Twenty five adult patients were prospectively imaged with a dedicated BB MRI sequence. A consensus qualitative BB MRI 'visibility score' for the confidence of demonstration of the mFN canal and the posterior canaliculus of the ChT was recorded, as well as a 'corresponding score' to determine whether the neural structures on BB MRI corresponded to the paths of the nerves on a previous CT study. Results/discussion: The BB MRI sequence was able to clearly delineate the course of mFN in 100% of cases and that of ChT in 72%, with their courses corresponding to those depicted on CT in almost all cases. Maximum intensity projections with 7 mm slabs provided the optimal simultaneous demonstration of mFN, ChT and round window along the posterior tympanotomy surgical approach. Conclusion: The proposed BB MRI sequence reliably depicts mFN and ChT in the majority of cases, with a performance comparable to that of CT. It is proposed that it will be a useful adjunct to MRI protocols as part of cochlear implant assessment in those centres where CT is not routinely performed.